MoS2-based nanosensors in biomedical and environmental monitoring applications. (20th July 2020) - Sha, Rinky; Bhattacharyya, Tarun Kanti
Abstract: Molybdenum disulfide (MoS2 ), an in-organic analogue of graphene with a distinctive structure, is being envisioned as the next generation 2D layered transition-metal dichalcogenide (TMD) nano-material towards greatly diversified sensing applications and nano-electronics. MoS2 and its composites have unlocked a new epoch in the fabrication of nano-sensors because of their exciting electrical, physico-chemical, catalytic features and biocompatibility including an adjustable band gap ranging from 0 (semimetal) to 2 eV (semiconducting), huge specific surface area, greatly exposed active sites on the plane edges, greater ionic conductivity as compared to the oxides, decent carrier mobility etc. This review (with 128 references) encompasses the properties, functionalization of MoS2 and their applications in nano-sensors for biomedical and environmental monitoring. To be precise, we discourse the modern developments of MoS2 and its nano-composites based sensors in major applications of biomedical and environmental monitoring, giving emphasis to the sensing performances which comprise of sensitivity, selectivity, durability, reproducibility, detection limit, and their viability in the real environs. Essential sensing mechanisms have been thoroughly conferred to get better perception into how MoS2 and its nano-composites contribute to the performance of each sensor. Wherever pertinent, shortcomings of the present approaches and future outlook have also been delineated. Highlights: Properties, functionalization of MoS2 and their applications in biomedical and environmental monitoring are discoursed. Underlying sensing mechanism of nano-sensors is presented to get better insight. Analytical performances of different sensing platforms were categorically displayed in two tables and compared. Wherever applicable, limitations of existing approaches and future outlook have also been outlined.